2015
DOI: 10.17645/pag.v3i1.271
|View full text |Cite
|
Sign up to set email alerts
|

The Expert-Executive Nexus in the EU: An Introduction

Abstract: Expertise has played a pivotal role in EU executives since the European Union (EU) was established, but its significance is arguably increasing and takes on new shapes. This issue explores the role and use of expert knowledge in decision-making in and by EU executive institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 66 publications
0
6
0
1
Order By: Relevance
“…They have (1) a shared set of normative and principled beliefs […]; (2) shared causal beliefs, which are derived from their analysis of practices […]; (3) shared notions of validity -that is, intersubjective, internally defined criteria for weighing and validating knowledge […]; and (4) a common policy enterprise -that is, a set of common practices associated with a set of problems to which their professional competence is directed. (Haas, 1992, p. 3) Research that explores the role of epistemic communities in EU internal policies has identified several political and economic variables (such as power dynamics and antipathies between stakeholders, economic disparities and politicisation of issues) that determine their input in the decision-making process (Gornitzka & Holst, 2015;Howorth, 2004;Verdun, 1999). Yet, despite these restrictions, in most cases the conclusion is that their impact is significant.…”
Section: Epistemic Communities and The Use Of Expert Knowledge In The Enpmentioning
confidence: 99%
“…They have (1) a shared set of normative and principled beliefs […]; (2) shared causal beliefs, which are derived from their analysis of practices […]; (3) shared notions of validity -that is, intersubjective, internally defined criteria for weighing and validating knowledge […]; and (4) a common policy enterprise -that is, a set of common practices associated with a set of problems to which their professional competence is directed. (Haas, 1992, p. 3) Research that explores the role of epistemic communities in EU internal policies has identified several political and economic variables (such as power dynamics and antipathies between stakeholders, economic disparities and politicisation of issues) that determine their input in the decision-making process (Gornitzka & Holst, 2015;Howorth, 2004;Verdun, 1999). Yet, despite these restrictions, in most cases the conclusion is that their impact is significant.…”
Section: Epistemic Communities and The Use Of Expert Knowledge In The Enpmentioning
confidence: 99%
“…Grupy interesu, a zwłaszcza te, które reprezentują wąskie sektory gospodarki, posiadają specjalistyczną wiedzę na temat specyfiki oraz problemów występujących w danej branży, której to wiedzy nie ma ustawodawca. Ich zasadniczą rolą jest zatem dostarczanie ustawodawcy specjalistycznego wkładu merytorycznego (Bouwen, 2002;Gornitzka, Holst, 2015). Trzecią funkcją, jaką grupy interesu pełnią w demokracji, jest funkcja kontrolna.…”
Section: Uwarunkowania Instytucjonalno-prawne Modelu Reprezentacji Interesówunclassified
“…In this, higher education can be seen as a policy area that is becoming more important but through this is also treated less special and facing increased political pressure to perform (Gornitzka & Maassen, 2014). Indeed, there are also many democratic legitimacy control issues at stake when discussing the usage of knowledge (Gornitzka & Holst, 2015), and questions about the relative and actual policy effectiveness of the 'scientific approach' and policy design (Chou & Ravinet, 2016;del Rio, 2016).…”
Section: Why Is the Case Of Higher Education So Interesting For Publimentioning
confidence: 99%